Carotid intima media thickness in type 2 diabetes mellitus with ischemic cerebrovascular stroke and its utility as a marker for predicting cerebrovascular disease - Shah, Mohita; Kothari, Prafful (International Journal of Advances in Medicine, 2022)
Background: In India, the national prevalence of diabetes mellitus (DM) is estimated at 18.2%. More than half of all diabetic deaths are accounted for by atherosclerotic disease leading to cardiovascular or cerebral complications. Intima media thickness (IMT), a measure of atherosclerotic vascular disease. It can easily be measured especially at the carotids by B mode ultrasonography, a relatively simple way representing a safe, precise, and reproducible measure. It has therefore been proposed as a non-invasive measure of predicting chances of cerebrovascular disease burden in adults. Methods: A total of 60 subjects in the age group of 30-75 years (M:F=37:23) were selected and divided into three groups, group C: Patients of either sex in the age group of 30-75 years with type 2 DM (T2DM) with or without hypertension with ischemic stroke demonstrated on CT scan. Group B: Age-matched T2DM patients of either sex without any prior history of transient ischemic attack or stroke. Group A: Age-matched normal individuals of either sex. The following groups of diabetic patients with stroke were excluded from our study: cardioembolic stroke, patients with hemorrhagic stroke, and patients with stroke due to secondary causes like trauma, impaired coagulation or tumor. Results: Average mean common carotid artery IMT (CCA-IMT) ranged from 0.72 to 0.97 mm across cohorts in people with diabetes. Patients with T2DM with ischemic stroke were found to have significantly higher prevalence of increased CIMT and a value greater than 0.8 mm was found to be associated with the occurrence of stroke. The mean CIMT was significantly higher in diabetic subjects compared to healthy subjects. Conclusions: A high CIMT is a surrogate and reliable marker of higher risk of cerebrovascular accidents amongst type 2 diabetic patients. Our study demonstrates the utility of carotid IMT as a simple non-invasive screening test for the assessment of atherosclerosis risk/prognosis in T2DM.